Green banana flour does not alter lipid and inflammatory profile of women overweight - Tavares da Silva, Sandra; Araújo dos Santos, Carolina; Cardoso Carraro, Júlia Cristina; Marques Rocha, José Luiz; Bressan, Josefina (O Mundo da Saúde, 2015)
The prevalence of chronic diseases such as dyslipidemia, overweight and complications related to the inflammatory state have increased worldwide. In this scenario, food products which claim to be beneficial in the treatment and/or prevention of these conditions arise as promises often having no scientific support. The green banana flour (GBF) has gained media attention as a possible promoter of beneficial health effects. However, there are no controlled studies on their real effects in human studies. The objective of this study was to analyze the effects of consumption of GBF in body weight, lipid pro- file, inflammatory parameters and food consumption in adult overweight women. An intervention study in which 25 adult overweight women consumed daily 20g of GBF during 45 days was carried out. The study protocol included anthropometric measurements, body composition, food intake, lipid profile and determination of serum inflammatory parameters. The mean age of participants was 34 years, with Body Mass Index of 27.7 kg/m². The consumption of FBV did not alter weight, body composition, lipid profile and inflammatory parameters. There was an increase in fiber intake (variation in median intake of 12,72g to 14,16g; p=0,031), although it has not achieved the needs of this nutrient (25g/day). Isolated consumption of FBV did not cause significant bodily and metabolic changes. The adoption of individual measures offer limited effects and should be discouraged as the only way of improving health.